Effect of Community Nutrition Rehabilitation Using a Multi-Ingredient Flour on theWeight Growth of Moderately Acute Malnourished Children in Benin - LALEYE, Flora; Nadia, Fanou; CHADARE, FLORA JOSIANE; MADODE, YANN EMERIC E.; KAYODE, A. PIERRE POLYCARPE; HOUNHOUIGAN, DJIDJOHO JOSEPH (My University, 2023)
Childhood malnutrition remains a public health problem in Benin. This study aimed to assess the nutritional potential of complementary food resources to accelerate the weight growth of moderately malnourished children hosted in learning and nutritional rehabilitation centers (LNRs) in eight municipalities in Benin. A multi-ingredient infant flour (i.e., FARIFORTI), composed of 35% corn flour (Zea mays), 15% malted sorghum (Sorghum bicolor), 30% soybean (Glycine max), 10% shelled and roasted peanuts (Arachis hypogeaea), 7% baobab pulp (Adansonia digitata), and 2% dried fried fish (Stolothrissa tanganyicae), was tested with 289 moderately malnourished children aged 6 to 59 months, selected in LNR sessions. Children were given the FARIFORTI flour porridge over 12 days (based on LNR protocol) in addition to other dishes based on local food resources. The weight and height of the children were measured at entry and at the end of the LNR sessions. The sensory evaluation indicated that the FARIFORTI flour was well-accepted by mothers (97%) and children (98%). The FARIFORTI porridge provided significantly higher intakes of carbohydrates and iron in children with weight gain compared to children without weight gain.
Keywords: malnutrition; food supplements; multi-ingredient porridge; LNR sessions; nutritional status